A modelagem matemática como estratégia de ensino e uma proposta para a abordagem de problemas reais via ajuste de curvas - Brito, Willian Henrique de (2019)
In this work, we make a brief rescue of the main facts that influenced the teaching of Mathematics in Brazilian schools during the twentieth century and the beginning of the twenty-first century. We highlight the potential of modeling activities to provide more reflective and contextualized learning and present different ways of conceiving and practicing mathematical modeling. We introduce the theme of curve fitting using the approximation method Least Squares for the particular case of polynomial functions and we propose a methodological approach of this resource in high school classes. We present an example of modeling activity in an interdisciplinary perspective in which curves fitting is naturally contemplated and foments the recognition of Mathematics as an important instrument of reasoning, representation, communication and argumentation.